Clinical and etiological characteristics of pneumonia in children with a poor outcome of infectious diseases - E. A. Kozyrev; I. V. Babachenko; V. E. Karev; D. A. Pimenov; E. V. Sharipova; E. D. Orlova; N. S. Tian (Журнал инфектологии)
Purpose: to study the clinical and etiological features of pneumonia in children with a poor outcome of infectious diseases.Materials and methods. The retrospective analysis of clinical, anamnestic, laboratory, instrumental data of 46 children who died from infectious diseases during the period from December 2009 to November 2019 was carried out, of which 26 patients had pneumonia at autopsy. The etiology of pneumonia was determined in vivo and postmortem using cultural, molecular genetic, serological methods and immunohistocytochemical examination of lung tissue. Pneumonia was classified into primary and secondary.Results. In patients with pneumonia in the structure of generalized infections (n=26) secondary forms prevailed (septic – 14 cases, ventilator-associated (VAP) – 5, aspiration – 2); primary pneumonia was detected in 5 children. Clinical polymorphism and frequent absence of typical symptoms of pneumonia (cough, shortness of breath, auscultatory and percussion changes) were shown, that led to intravital underdiagnosis of pneumonia in 31% of patients. The probable etiology of pneumonia was detected in vivo and postmortem in 58% and 98% of cases respectively. S. pneumoniae (40%) and H. influenzae type b (40%) were main pathogens in primary pneumonia, N. meningitidis (36%) and S. pneumoniae (29%) – in septic pneumonia, commensals of naso- and oropharynx (S. salivarius) – in aspiration pneumonia, nosocomial bacteria (S. aureus and coagulase-negative staphylococci) – in VAP. In children with HIV infection, pneumonia was associated with opportunistic pathogens (P. jirovecii, C. neoformans). In 87% of cases polymicrobial associations were found in lower airways, that makes it difficult to identify the main causative agent of pneumonia.Conclusions. Most of symptoms of pediatric pneumonia in the structure of generalized infections are nonspecific. Post-mortem study improves the etiological verification of pneumonia and allow to suggest the most pathogenetically and thanatogenetically significant pathogen.